Gender segregation in the Barbadian labour market 1946 and 1980 - Lynch, Roslyn (Consortium Graduate School of Social Sciences MonaJA, 1995)
Identifies and compares trends in the employment of men and women in Barbados between 1946 and 1980. Documents the degree of gender segregation which existed in the labour market at two periods in time and the shifts which have occured over the period as a result of changes in the island's economy.